Tinjauan Yuridis Konsep Kepentingan Umum dan Dasar Penghitungan Ganti Rugi dalam Proses Pengadaan Tanah untuk Kepentinan Pembangunan - Harris Yonatan Parmahan Sibuea (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2010)
The State control of the land dose not mean that the State owns the land, but rather the State regulate land use through the development of which is directed to achieve prosperity for all citizens. Land acqusition for development is one way to increase prosperity for the people, but the avaible land is extremely limited. Goverment policies as legal foundation to acquire the land has not been effective and no longer appropiate to solve the problem for the implementation of land acqusition for development. These problems include the concept of public interest must clearly type that devoted to the interests of the people and the market value of land should be the basic for calculating damages in the process of land acqusition for development. It is time uor country has a higher legal foundation for regulating the provision of land for development to improve people’s welfare. The author in the process of the Draft Law on Land Acquisition for Development Interest.